Complicaciones intraoperatorias de la facoemulsificación: Características clínicas predisponentes y efecto sobre la agudeza visual final - Palacios Vergara, Raisa Lorena Isabel (2022)
Cataract is the leading cause of blindness worldwide. The only treatment available is surgery, which is not exempt from intraoperative complications that could affect the visual outcome. Certain characteristics may predispose to such complications, such as mature cataract, pseudoexfoliation, small-pupil, and axial length > 26mm. Knowing them will allow designing preventive measures to achieve increasingly efficient surgeries. Objectives: To determine the clinical characteristics associated with the presence of intraoperative complications of phacoemulsification and their effect on final visual acuity. Methods: Medical records of patients who underwent cataract surgery between January 2019 and December 2019 and who meet the inclusion and exclusion criteria will be reviewed. Mean (standard deviation) or frequency (percentage) will be used to describe the summary data. Analysis for quantitative variables will be performed with Student’s t test and for qualitative variables we will use Chi-square test or Fisher's exact test. P < 0.05 will be considered as statistically significant.